Day hospital care for eating disorders: review of the literature and preliminary findings at AMBULIM, Institute of psychiatry, University of São Paulo - Salzano, Fábio Tapia (2003)
The authors revised the literature about treatment in day-hospital (DH) of psychiatric disorders in general and more specifically about eating disorders, pointing out historical aspects, indications and contra-indications of DH treatment, clinical efficacy and financial advantages. They also described DH programs around the world, including the DH of AMBULIM-IPqHCFMUSP (São Paulo, SP, Brasil).